Exciton Bose-Einstein Condensation in Double Walled Carbon Nanotubes. (15th June 2017) - Bondarev, Igor V.; Popescu, Adrian
ABSTRACT: We demonstrate theoretically the possibility for the Bose-Einstein condensation of excitons in properly selected double walled carbon nanotube structures. The condensation mechanism is enabled by the interaction of excitons residing on one tubule with the near-field generated by the plasmon mode of the other coaxial tubule, resulting in new hybridized bosonic quasiparticles called exciton-plasmons. We derive the dispersion relation for the exciton-plasmons, and calculate the exciton participation rate in the exciton-plasmon condensate. The requirements for forming the appropriate double walled carbon nanotube combinations capable of the optimum exciton-plasmon coupling regime needed to realize the condensation effect, as well as the possibility of experimental observation of the phenomenon, are discussed.